Bilingualism: The Interaction of Neurobiological, Social, and Educational Factors in Second Language Acquisition (SLA) - Aprinalistria, Aprinalistria (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Second Language Acquisition (SLA) is a complex and multidimensional field of study, involving factors such as age, environment, motivation, and social context. This study aims to review recent developments in SLA theory and practice, with a focus on variability, plasticity, and the influence of age in second language acquisition and bilingualism. The review also explores the social dimensions and multilingual processes within transnational contexts. The methodology follows PRISMA guidelines. Literature searches were conducted in academic databases such as Scopus, PubMed, and Google Scholar, using keywords such as "second language acquisition," "bilingualism," "age of acquisition," and "multilingual socialization." Articles published between 2018 and 2023 were selected based on relevance and quality. The selection process involved identification, screening, and quality assessment of studies that met the inclusion criteria. Relevant data were extracted and analyzed thematically. Results indicate that age plays a crucial role in modulating plasticity and variability in SLA, with critical periods influencing second language proficiency. Factors such as motivation, self-confidence, and social environment also significantly contribute to successful second language learning. Additionally, recent research emphasizes the importance of social and multilingual dimensions in global contexts, including translanguaging practices and intercomprehension. This review also identifies challenges and inequalities faced by language learners from minority backgrounds. These findings highlight the need for a more holistic and inclusive approach to SLA research and teaching, considering sociopolitical contexts and multilingual identities. Practical implications include the development of more flexible curricula and teaching methods that support language learning in diverse environments. Further research is needed to explore the interaction between neurobiological, cognitive, and social factors in SLA.